Marketing Mix Affecting Consumers in Purchasing at Refill Shops in Mueang Chiang Mai District - Fubin, Wariya; Pichayakul, Pichayalak (Community and Social Development Journal, 2022)
Refill shop refers to a shop where customers bring their own containers to fill and purchase products with a purpose of preserving the environment by reducing waste. The purpose of this research was to study the marketing mix that affects consumers in shopping at refill shops in Mueang Chiang Mai District. This research is quantitative research. A questionnaire was used to collect data. The samples included 158 customers who had shopped at any refill shop located in Mueang Chiang Mai District. The data collection took place in the 5 selected refill shops in Chiang Mai. The researchers applied descriptive statistics. The study revealed that most respondents were female, single, age range 20-30 years old, graduated with bachelor's degree, worked as company employees, average monthly income of 10,000 - 20,000 baht, shopped at a refill shop 1-2 times per month. Regarding the marketing mix factors, the respondents ranked all marketing mix factors at high to the highest levels. The ranked factors included product (4.21), price (3.98), place (3.94), and promotion (3.53), respectively.